2010
DOI: 10.1002/cphc.200900964
|View full text |Cite
|
Sign up to set email alerts
|

Redox Activity and Structural Transition of Heptyl Viologen Adlayers on Cu(100)

Abstract: The redox behaviour and potential-dependent adsorption structure of heptyl viologen (1,1'-diheptyl-4,4'-bipyridinium dichloride, DHV(2+)) on a Cu(100) electrode was investigated in a chloride-containing electrolyte solution by cyclic voltammetry (CV) and in situ electrochemical scanning tunneling microscopy (EC-STM). The dicationic DHV molecules generate a few pairs of current waves in CV measurements which are ascribed to two typical one-electron transfer steps. STM images obtained in a KCl-containing electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Ultra-thin epitaxial film systems exhibit a variety of interesting properties due to the strong correlation between the electronic structure of the film and its morphology, strain, and defect structure [1,2,3,4,5,6,7,8,9,10]. Structural studies of fcc/fcc systems provide a great deal of information on the connection between the geometrical properties of the adsorbed atomic layers and the atomic arrangements of the substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-thin epitaxial film systems exhibit a variety of interesting properties due to the strong correlation between the electronic structure of the film and its morphology, strain, and defect structure [1,2,3,4,5,6,7,8,9,10]. Structural studies of fcc/fcc systems provide a great deal of information on the connection between the geometrical properties of the adsorbed atomic layers and the atomic arrangements of the substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from HOPG, Jiang and coworkers have recently observed a stripe pattern of adsorbed HV •+ on a chloride modified Cu(100) electrode surface by in situ STM. 35 In their model, the main molecular axis of HV •+ is parallel to the surface in a side-on configuration, exhibiting the formation of π-stacked polymer chains.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption layers of organic molecules on electrode surfaces frequently exhibit sharp phase transitions triggered by the potential change. A better understanding of the potential-driven phase transitions together with the molecular level adsorption structures would lead us to the development of devices that show drastic, sharp, and chemically reversible responses to the potential change at electrified interfaces. Viologens bearing long alkyl chains are among the molecules that exhibit faradaic phase transition, in many cases of the first-order, on several electrode surfaces. The phase transition is represented by sharp spike peaks in cyclic voltammograms (CVs).…”
Section: Introductionmentioning
confidence: 99%
“…There have also been some reports on the adsorption of viologens at copper and copper modified surfaces. Jiang et al [10] have reported the potential-dependent adsorption of heptyl viologen on a Cu(100) surface in a chloride-containing electrolyte. In the absence of the viologens, a highly ordered chloride adlayer was observed on the Cu(100).…”
Section: Introductionmentioning
confidence: 99%